A handbook to the reception of Ovid - Miller, John F., 1950-; Newlands, Carole Elizabeth (Chichester, West Sussex, UK : Malden, MA : Wiley-Blackwell, 2014)
A Handbook to the Reception of Ovid presents more than 30 original essays written by leading scholars revealing the rich diversity of critical engagement with Ovid's poetry that spans the Western tradition from antiquity to the present day. -Offers innovative perspectives on Ovid's poetry and its reception from antiquity to the present day -Features contributions from more than 30 leading scholars in the Humanities. -Introduces familiar and unfamiliar figures in the history of Ovidian reception. -Demonstrates the enduring and transformative power of Ovid's poetry into modern times.
Ovid's self-reception in his exile poetry / K. Sara Myers -- Modeling reception in Ovid's Metamorphoses: Ovid's epic Cyclops / Andrew Feldherr -- Ovidian myths on Pompeiian walls / Peter E. Knox -- Ovid in Flavian occasional poetry (Martial and Statius) / Gianpiero Rosati -- Poetae ovidiani: Ovid's Metamorphoses in imperial Roman epic / Alison Keith -- Ovid in Apuleius' Metamorphoses / S.J. Harrison -- A poet between two worlds: Ovid in late antiquity / Lan Fielding -- Commentary and collaboration in the medieval allegorical tradition / Jamie C. Fumo -- The mythographic tradition after Ovid / Gregory Hays -- Ovid's exile and medieval Italian literature: the lyric tradition / Catherine Keen -- Venus's clerk: Ovid's amatory poetry in the Middle Ages / Marilynn Desmond -- The metamorphosis of Ovid in Dante's Divine comedy / Diskin Clay -- Ovid in Chaucer and Gower / Andrew Galloway -- Ovid's Metamorphoses and the history of baroque art / Paul Barolsky -- The poetics of time: the Fasti in the Renaissance / Maggie Kilgour -- Shakespeare and Ovid / Sean Keilen -- Ben Jonson's light reading / Heather James -- Love poems in sequence: the Amores from Petrarch to Goethe / Gordon Braden -- Don Quixote as Ovidian text / Frederick A. De Armas -- Spenser and Ovid / Philip Hardie -- Ovidian intertextuality in Ariosto's Orlando Furioso / Sergio Casali -- "Joy and harmles pastime": Milton and the Ovidian arts of leisure / Mandy Green -- Ovid translated: early modern versions of the Metamorphoses / Dan Hooley -- Ovid in restoration and eighteenth-century England / James M. Horowitz -- The influence of Ovid in opera / Jon Solomon -- Ovid in Germany / Theodore Ziolkowski -- Ovid and Russia's poets of exile / Andrew Kahn -- Alter Ovid: contemporary art on the hyphen / Jill H. Casid -- Contemporary poetry: after after Ovid / Sarah Annes Brown -- Ovid's "biography": novels of Ovid's exile / Rainer Godel -- Ovid and the cinema: an introduction / Martin M. Winkler.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Ovid, -- 43 B.C.-17 A.D. or 18 A.D. -- Criticism and interpretation; Ovid, -- 43 B.C.-17 A.D. or 18 A.D; POETRY -- Ancient, Classical & Medieval; Literary criticism; Electronic books; Criticism, interpretation, etc